La autoestima en el aprendizaje educativo de los estudiantes de tercer año de educación general básica de la escuela ciudad de Ventanas en el periodo 2021-2022 - Monserrate Fajardo, Julieta del Carmen (2022)
It was observed that the self-esteem factors that intervene in the good academic performance of the students are self-confidence, ease of socializing, inspiring confidence, respect from others, satisfied with themselves, being cheerful, kind, reflecting on the satisfaction they have with their chosen career. All this indicates that the third year students are characterized in their way of being by maintaining an adequate level of self-esteem that is linked to their academic performance. Likewise, low self-esteem affects the poor academic performance of students, that is, they show little motivation, they are not organized, nor do they dedicate enough time to study. Therefore, the working hypothesis is accepted, stating that the student's self-esteem is significantly related to their academic performance. In this context, the article that is presented as a reflection, aims to give an account of how, from the educational level, scenarios are provided for the construction of self-esteem, a key factor to face daily situations and to overcome the obstacles that arise. when interacting with teachers, peers and people around him. Based on the above, it is proposed to disseminate the results obtained to serve as a basis for future research, to include self-esteem workshops that allow the student to raise and maintain their level, improving their personal development, in such a way that they achieve adequate academic performance. and professional success.